Women in Pink: Why Pink Considered as Feminine, Soft, Delicate, and Even Silly? - Nadira Aqilla Tsaqib; Nayra Khairina Zain; Oci Fifi Aisah Saudina (GLOBAL SCIENTS PUBLISHER, 2026)
Colors are often associated with gender stereotypes in society, especially pink for women and blue for men. Pink is commonly perceived as feminine, soft, delicate, emotional, and sometimes even silly, while blue is associated with masculinity, strength, and rationality. These stereotypes have become socially normalized through culture, media, fashion, and advertising. This article discusses how the concept of gendered colors was socially constructed and how it affects both women and men in everyday life. The article also examines the role of toxic masculinity in shaping society’s expectations toward men who engage with feminine-associated colors such as pink. This article uses a qualitative descriptive method to analyze the social construction of gendered colors, especially the association of pink with femininity and blue with masculinity. The findings show that the meanings attached to colors are not natural, but socially created and continuously reinforced through media representation and cultural norms. Furthermore, color stereotypes contribute to limiting self-expression and maintaining traditional gender expectations. Therefore, this article argues that colors should not be restricted by gender labels because they are forms of personal expression rather than indicators of masculinity or femininity.